The Determination of The European Union in The International Promotion of Human Rights (Vallis Aurea, 2021)
This paper aims to explain the legal, political and moral obligation of the European Union institutions in the promotion, advancement, respect, and implementation of human rights and freedoms as a universal value, and above all as binding legal- political principles during their efforts in relations with actors both inside and outside the EU.This research work simultaneously analyzes and interprets international legal rules that regulate human rights.Moreover, the cases and means in promoting the human rights used by the European Union in different cultural regions have been compared and analyzed as well as the possibility of changing the approach of EU policy towards countries where the highest level of resistance exist in the accepting of such values.